Evaluation of the long-shelf life honey milk As a storage media for preservation of avulsed teeth - Ali Nozari; Tahere Esmaeilpour; Soleiman Fijan; Mahin Salmannejad (Babol University of Medical Sciences, 2013)
Introduction: Tooth avulsion is defined as the complete displacement of the tooth from its alveolar socket which causes damage to the periodontal ligament structure, cementum, alveolar bone, gingiva, and dental pulp. The purpose of this study was to determine the ability of long-shelf life honey milk to serve as a temporary storage medium for the maintenance of periodontal ligament (PDL) cell viability on avulsed teeth. Methods: PDL cells were obtained from premolars extracted for orthodontic purposes which were clinically healthy and had healthy gingiva (i.e. not inflamed).Then, 8×10³ cells were seeded in each well of 96-well plate. and Afterwards treated with long-shelf life milk and honey milk, Hank's Balanced Salt Solution (HBSS) and fresh milk. Different incubation periods were 1, 3, 6, and 9 hours. Dulbecco's Modified Eagle Medium (DMEM) and dry medium were considered as positive and negative control media, respectively. Cell viability was determined by using the MTT (Thiazolyl Blue Tetrazolium Bromide) assay. Data were statistically analyzed with one-way anova, two-way anova and post hoc Scheffe tests. A level of p≤0.05 was accepted as statistically significant Results: The results indicate that all media performed significantly better in maintaining PDL cell viability than the negative control at all time periods. (p≤0.001) After 9 hours, Percentage of viable PDL cells in long-shelf life honey milk, long-shelf life milk and HBSS were 82±0.82, 75±8.13 and 87±2.78 respectively. Furthermore cells' viability in both long-shelf life honey milk and HBSS was significantly better than fresh milk medium (p=0.003). Moreover, the results of One-way ANOVA showed long-shelf life honey milk were more effective in preserving the PDL cell viability as well as HBSS after 9 hours. Conclusions: According to the study results, long-shelf life honey milk considered as appropriate storage media which are comparable to HBSS. These media are not only able to keep more cells viability after 9h compared to the expensive commercial solutions, but are also be easily accessible.